PENINGKATAN SIKAP PERCAYA DIRI DAN HASIL BELAJAR SISWA KELAS V SDN TLOGOADI DENGAN MODEL PROBLEM BASED LEARNING (PBL) TAHUN PELAJARAN 2022/2023 - LENDY HUDA PRABOWO; RISHE PURNAMA DEWI; JAROT PRAKOSO (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
This study aims to: (1) describe the increase in students' self-confidence in learning science class V through the application of the Problem Based Learning (PBL) learning model (2) describe the increase in science learning outcomes for class V students using the Problem Based Learning (PBL) learning model. This research is a Classroom Action Research consisting of two cycles that go through the stages of planning, implementing, observing, and reflecting. Techniques used for data collection using interviews and tests. The subjects in this study were 36 students in class V SDN Tlogoadi. The object of this research is self-confidence and learning outcomes. Data obtained through observation and tests. The data analysis technique used is quantitative analysis. The results showed that the application of the Problem Based Learning learning model could increase students' self-confidence, which was initially an average of 35.62% increased to 56.94% in the first cycle; and increased to 80.03% in the second cycle. For the application of the Problem Based Learning model can improve the learning outcomes of students; initially averaged 55; increased to 78 in the first cycle; then increased to 83 in cycle II. Learning Problem Based Learning can increase students' self-confidence and student learning outcomes in science subjects. ABSTRAK Penelitian ini bertujuan: (1) mendeskripsikan peningkatan percaya diri siswa dalam belajar IPA kelas V melalui penerapan model pembelajaran Problem Based Learning (PBL) (2) mendeskripsikan peningkatan hasil belajar IPA siswa kelas V menggunakan model pembelajaran Problem Based Learning (PBL). Penelitian ini merupakan Penelitian Tindakan Kelas terdiri dari dua siklus yang melalui tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik yang digunakan untuk pengumpulan data menggunakan wawancara dan tes. Subjek dalam penelitian ini ada 36 siswa pada kelas V SDN Tlogoadi. Objek penelitian ini merupakan sikap percaya diri dan hasil belajar. Data didapatkan melalui observasi dan tes. Teknik analisis data yang digunakan adalah analisis kuantitatif. Hasil penelitian menunjukkan dalam penerapan model pembelajaran Problem Based Learning dapat meningkatkan sikap percaya diri siswa yang awalnya rerata 35,62% meningkat menjadi 56,94% pada siklus I; dan meningkat menjadi 80,03% pada siklus II. Untuk penerapan model Problem Based Learning dapat meningkatkan hasil belajar dari peserta didik; awalnya rata – rata 55; meningkat menjadi 78 pada siklus I; kemudian meningkat 83 pada siklus II. Pembelajaran Problem Based Learning dapat meningkatkan rasa percaya diri siswa dan hasil belajar siswa pada mata pelajaran IPA.